Philosophy of religion after "religion" - Rodgers, Michael Ch.; Amesbury, Richard (Religion in philosophy and theology, 2023)
Cover -- Title -- Preface -- Contents -- Introduction: Making the Reflexive Turn in Philosophy of Religion - Richard Amesbury -- »Religion« under Erasure: Why the Concept is Problematic and Why We Still Need It - Sonia Sikka -- Why Philosophers of Religion Don't Need »Religion« - At Least Not for Now - Timothy D. Knepper -- An Essentialist in Critical Religion Land, Or, How Fitzgerald's Deconstructive Genealogy of Religion Is Compatible with an Essentialist Concept of Religion - Dwayne Tunstall -- Vagueness and Its Virtues: A Proposal for Renewing Philosophy of Religion - J. Aaron Simmons -- Race and the Philosophy of Religion - Vincent Lloyd -- Nothingness and Self Transformation: Kim Iryŏp, Tanabe Hajime, and Jacques Derrida on Relgious Practice - Jin Y. Park -- Whether Religion Is a Proper Subject of Study - Robert Cummings Neville -- Contributors -- Subject Index -- Author Index.